The Impact of the Russia-Ukraine War and Its Implications for Indonesia's Economic Resilience Strategy - Yulivan, Ivan; Mahroza, Jonni; Widjayanto, Joni; Prakoso, Lukman Yudo; Setiadi, Muhammad Ikmal (PT FORMOSA CENDEKIA GLOBAL, 2024)
The world economy will feel the impact of rising commodity prices due to the crises in Ukraine and Russia. In addition, inflation around the world will increase due to rising food and energy prices. In addition, the imposition of economic sanctions on Russia by the United States and its allies has further exacerbated not only the armed conflict but also the world economic recovery. This qualitative research approach was implemented through literature reviews and field studies. The global economy, including Indonesia, will be greatly affected by the diplomacy carried out by the Indonesian government in response to Russia's military action against Ukraine. Worldwide disruption of food and energy supplies will occur as a result of this conflict. In the midst of increasing prices of various commodities and crude oil on the international market, the Indonesian government is expected to implement proactive steps to manage inflation.